2003
DOI: 10.1034/j.1399-3054.2003.00181.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenylpropanoid deficiency affects the course of plant acclimation to cold

Abstract: The effects of phenylpropanoid deficiency on plant growth, photosynthetic efficiency of the photosystem II and freezing tolerance of leaves were studied during acclimation of winter oilseed rape plants (Brassica napus L. var. oleifera L. cv Jantar) at low temperature. Application of 2-amino-2-indanophosphonic acid inhibited phenylalanine ammonialyase (E.C. 4.3.1.5) activity by about 90%. This was followed by a marked reduction of soluble phenolics (in particular hydroxycinnamic acids) and anthocyanins in leave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
88
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(95 citation statements)
references
References 53 publications
5
88
0
2
Order By: Relevance
“…Plant phenolics are naturally occurring substances, characterized as aromatic metabolites, many of which play physiological roles such as antibacterial, antiviral, anticancer agents and scavengers of most types of oxidizing agents (Solecka and Kacperska 2003). Under biotic and abiotic stresses such as pathogen attack, physical wounding, and UV-light exposure, plants can induce a defense response and increase secondary metabolite levels (Ali and others 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Plant phenolics are naturally occurring substances, characterized as aromatic metabolites, many of which play physiological roles such as antibacterial, antiviral, anticancer agents and scavengers of most types of oxidizing agents (Solecka and Kacperska 2003). Under biotic and abiotic stresses such as pathogen attack, physical wounding, and UV-light exposure, plants can induce a defense response and increase secondary metabolite levels (Ali and others 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic compounds are naturally occurring substances in plants, many of which are thought to play physiological roles such as antibacterial, antiviral, anticancer agents and scavengers of most types of oxidizing molecules [1]. Under biotic and abiotic stresses such as pathogen attack, physical wounding, and UV-light exposure, plants can induce a defense response and increase secondary metabolite levels [2].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, enzymes such as phenylalanine ammonia lyase (PAL; EC 4.3.1.5), cinnamate-4-hydroxylase (C4H; EC 1.14.13.11) and 4-coumarate:coenzyme A ligase (4CL, EC 6.2.1.12) are considered to be crucial to phenylpropanoid metabolism. A number of reports have shown that phenylpropanoid derivatives are capable of protecting plants against various biotic (infection by viruses, bacteria, fungi) and abiotic (low and high temperatures, UV-B light, wounding) stresses (Sgarbi et al 2003;Solecka and Kacperska 2003). Stilbene synthase (STS) (EC 2.3.1.95) catalyses the last step of the phenylpropanoid biosynthesis pathway leading to the formation of stilbene phytoalexins.…”
Section: Introductionmentioning
confidence: 99%